2009
DOI: 10.1515/jpem.2009.22.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Atorvastatin in Diabetes Trial (PADIT): A Pilot Study to Determine the Effect of Atorvastatin on Arterial Stiffness and Endothelial Function in Children with Type 1 Diabetes Mellitus

Abstract: Fifty-one children with type 1 diabetes mellitus (DM1) participated in a double blinded, randomized, cross-over pilot study to determine whether 12 weeks of daily atorvastatin (20 mg daily) would reduce arterial stiffness and improve endothelial function. Secondary analysis demonstrated potential reduction of arterial stiffness following atorvastatin therapy (p = 0.06). Additional long-term prospective studies with larger numbers of patients are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 6 publications
0
30
0
3
Order By: Relevance
“…Certain drugs have been successfully used for the management of ED and AS and therefore for the prevention of potential DM complications. [12][13][14] Early diagnosis and early management of ED and AS may reduce diabetic complications. In this study, we aimed to detect ED and AS and determine the association with diastolic dysfunction in children with DM who had no complications.…”
Section: Discussionmentioning
confidence: 99%
“…Certain drugs have been successfully used for the management of ED and AS and therefore for the prevention of potential DM complications. [12][13][14] Early diagnosis and early management of ED and AS may reduce diabetic complications. In this study, we aimed to detect ED and AS and determine the association with diastolic dysfunction in children with DM who had no complications.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have specifically examined the effect of intensive pharmacological therapy on CVD risk factor reduction in children with T1DM, although 1 study suggested a trend toward improved endothelial function after 12 weeks of atorvastatin 20 mg/d. 231 The American Academy of Pediatrics, the American Heart Association, and the ADA recognize patients with DM, and particularly T1DM, as being in a higher-risk group who should receive more aggressive risk factor screening and treatment than nondiabetic children. 125,228,229,232 The National Heart, Lung, and Blood Institute Expert Panel on Integrated Guidelines for Cardiovascular Health and Risk Reduction in Children and Adolescents has specific lifestyle and pharmacotherapy recommendations for children with lipid abnormalities and specifies management for children with T1DM.…”
Section: Cvd Risk Factors In Children With T1dmmentioning
confidence: 99%
“…5,6,61,62,64 However, it is important to note that FMD has been previously shown to be significantly associated with arterial stiffness under a number of conditions and disease states. [122][123][124][125][126] Wright et al 127 noted that this association was weak and suggested that measurements of arterial stiffness should not replace FMD. However, they used neither AIx nor cfPWV (the 'gold standard') as arterial stiffness measurements in their study.…”
Section: Mechanismsmentioning
confidence: 99%